2018
DOI: 10.3390/su10103750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information and Communication Technology Infrastructure on Economic Growth: An Empirical Assessment for the EU Countries

Abstract: The accelerated development of information and communication technology (ICT) over the past two decades has encouraged an increasing number of researchers to examine and measure the impact of this technology on economic growth. Our study aims to identify and evaluate the effect of using ICT infrastructure on economic growth in European Union (EU) countries for a period of 18 years (2000–2017). Using panel-data estimation techniques, we investigate empirically how various indicators of ICT infrastructure affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 43 publications
10
105
2
7
Order By: Relevance
“…Along the same lines, Toader, Firtescu, Roman, and Anton [32] identify a number of investigations that show the positive impacts of ICT on the economy as a whole. For our study, we chose those directly related to sustainable development (Table 1).…”
Section: Ict and Sustainable Environmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Along the same lines, Toader, Firtescu, Roman, and Anton [32] identify a number of investigations that show the positive impacts of ICT on the economy as a whole. For our study, we chose those directly related to sustainable development (Table 1).…”
Section: Ict and Sustainable Environmentmentioning
confidence: 86%
“…[35] Access of human capital through teleworking [36] Fast and effective business communication: reducing costs and increasing productivity. [37] Source: Toader, Firtescu, Roman, and Anton (2018) [32].…”
Section: Impact Of Ict On Sustainability Authormentioning
confidence: 99%
“…In many works of literature, GDP has been widely known as a predictor of ICT adoption in many countries. Toader, Firtescu, Roman, and Anton (2018) argued that GDP played a significant role in ICT adoption. Similarly, Mimbi and Bankole (2016) found that the greater the GDP of a country was, the higher the adoption and usage of ICT were.…”
Section: H5: Asian Countries With High Long Term Orientation Are Pronmentioning
confidence: 99%
“…ICT is the use of electronic and computer-based technologies to access information and is used to connect and communicate with the rest of the world. During the previous two decades, a significant number of studies have been conducted to focus on the influence of ICT development on the growth of productivity (Chun & Nadiri, 2008;Timmer & Van Ark, 2005) and also on the expansion of economic activities and growth (Mansell & Wehn, 1998;Pohjola, 2000;Ishida, 2015;Erumban & Das, 2016;Toader, Firtescu, Roman, & Anton, 2018;Bahrini & Qaffas, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%